Pengaruh Lingkungan Kerja Fisik, Kompensasi, dan Beban Kerja terhadap Turnover Intention Karyawan pada PT. Agri Tanimas Selaras - Indriani Hutagalung; Taufik Risal (Lembaga Pengembangan Kinerja Dosen, 2025)
This study uses a quantitative method approach that focuses on cause-effect relationships. This study aims to analyze the influence of the physical work environment, energy, and workload on employee turnover at PT. Agri Tanimas Selaras. This study was conducted at PT. Agri Tanimas Selaras located at Jl. Tangkahan, Medan Labuhan District, Medan City, North Sumatra, 20251. In this study, the general population is defined as all employees of PT. Agri Tanimas Selaras. While the target population is all permanent employees of PT. Agri Tanimas Selaras, totaling 85 people. The data collection technique for this study uses a questionnaire. To test the research instrument, validity and reliability tests are used. The analysis method used is the T test and F test. The results of the T test show that the physical work environment has a negative and significant effect on employee turnover, which means that the better the physical work environment, the lower the employee's desire to leave the company. Conversely, costs and workload do not have a positive and significant effect on employee turnover, which indicates that these two variables do not directly affect employee desire to leave the company. However, the F-test results show that simultaneously, the physical work environment, reserves, and workload have a positive and significant effect on employee turnover. This finding demonstrates the importance of a holistic approach to managing factors affecting employee retention.